2012
DOI: 10.1186/1749-799x-7-2
|View full text |Cite
|
Sign up to set email alerts
|

Hook plate fixation of acute displaced lateral clavicle fractures: mid-term results and a brief literature overview

Abstract: BackgroundThe clavicle hook plate achieves like most other operative techniques, a high percentage of union and a low percentage of complications however concerns about long term complications still exist, particularly the involvement of the acromioclavicular joint.MethodsTo evaluate the results and long term effects in use of this plate we performed a retrospective analysis with a mean follow up of 65 months (5.4 years) of 28 consecutive patients with acute displaced lateral clavicle fractures, treated with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
83
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(88 citation statements)
references
References 28 publications
2
83
0
3
Order By: Relevance
“…Complications reported with this design have also been relatively frequent, including implant failure and metaphyseal fracture, impingement, rotator cuff tears or even hook migration and acromial fracture as the implant penetrates the subacromial space and require plate removal. It is therefore important to exercise caution when using hook plate [6][7][8][9][10][11][12][13]. In a recent study, Tan et al [26] reported 74 % of patients in the hook plate group had mild to severe shoulder pain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Complications reported with this design have also been relatively frequent, including implant failure and metaphyseal fracture, impingement, rotator cuff tears or even hook migration and acromial fracture as the implant penetrates the subacromial space and require plate removal. It is therefore important to exercise caution when using hook plate [6][7][8][9][10][11][12][13]. In a recent study, Tan et al [26] reported 74 % of patients in the hook plate group had mild to severe shoulder pain.…”
Section: Discussionmentioning
confidence: 99%
“…Since not all studies reported the functional outcome scores of the distal clavicle fractures and they used different functional evaluation instruments, it was difficult to analyse and compare the function between the different treatment modalities. Consequently, we reviewed and compared the functional outcome scores evaluated by Constant score between the hook plate group (nine studies) [6,7,[9][10][11][12][13]31, present study] and the locking plate group (eight studies) [14][15][16][17][18][19][20]30, present study] in distal clavicle fractures. The mean Constant scores were 91.9 and 93.6 in the hook plate and locking plate groups, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, later reports showed increased incidence of complications such as subacromial impingement, rotator cuff ruptures, acromion fractures, acromial osteolysis and pain. 10 The technique presented in this study provides rigid fixation of the distal clavicle fracture itself and does not limit the Fig. 1 e a) Preoperative X-ray.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors 1,7,8 reported high rates of nonunion or delayed union (67e75%) in Neer type II distal clavicle fractures with conservative treatment. Many surgical methods have been introduced for distal clavicle fractures, including, transacromial Knowles pins, 9 hook-plate fixation, 5,10 and coracoclavicular stabilization with suture loops, 11 or screws. 12 Techniques using internal fixation that includes rigid coracoclavicular or acromioclavicular fixation have the disadvantage of interfering with the normal rotational movement of the clavicle in relation to the coracoid and acromion.…”
Section: Discussionmentioning
confidence: 99%